Margaret Bonds - Cooper, John Michael 1962- (Oxford University Press, 2025)
Composer, pianist, teacher, & social-justice activist Margaret Bonds fought against racism, sexism, & economic injustice throughout her career, amassing a portfolio of social-justice compositions unrivalled in eloquence & originality which challenged longstanding barriers between Black & White, male & female, popular & classical. During her lifetime the political economy of music publishing consigned most of her music to manuscript dissemination, & since her death her success in transcending the barriers she faced as an African American & a woman has been obscured by the forces of racism & sexism in concert life, which, together with White- & male-dominated music historiography, have viewed her life & work through the lens of specious, racist, & sexist tropes. This book draws on an unprecedented mass of archival evidence to set aside those tropes & offer a fresh portrait of Margaret Bonds
Includes bibliographical references and index
Keywords: Bonds, Margaret; Biography / ukslc; Biography & non-fiction prose / thema; African American women composers / Biography; African American women musicians / Biography; African American women civil rights workers / Biography; Composers / United States / Biography; Pianists / United States / Biography; Civil rights workers / United States / Biography